Potential use of Pump as Turbine Coupled to Self-Excited Induction Generator for Micro-hydro Cooking and Cooling Applications - Nyirenda, Emanuel J.; Nielsen, Torbjorn K.; Kihedu, Joseph H.; Kimambo, Cuthbert Z.M. (Tanzania Journal of Engineering and Technology, 2025)
Clean cooking and efficient cooling in developing countries have recently become areas of great focus. Further, the environmental impact of flooding in high-capacity hydroelectric plants has become a major concern. As a result, there is growing emphasis on developing sustainable and decentralized energy solutions, focusing on the potential of micro-hydro systems, especially in rural and remote areas. Although there are several alternative energy generation methods, their application is not straightforward. One of the latest technologies under research is using pumps as turbines coupled to an induction generator. This paper explores through a rigorous experimental approach the possibility of using a pump as turbine (PAT) coupled with a self-excited induction generator (SEIG) as an alternative energy source for heating, lighting, and cooling applications. The 1.5 kW delta-connected induction generator was excited by three 50 µF starconnected capacitors. The cooking and cooling apparatus was represented by a resistive element with a fixed resistance and inductance seen by the generator. The results show that the PAT-SEIG system produced the required 240 V, which is sufficient to power ten 50 W LED bulbs or power a compressor for a cooling system. The study has demonstrated that PAT-SEIG can offer an alternative, cost effective solution for generating electricity to power cooking or cooling appliances